An MCDM framework for assessment of social sustainability indicators of the freight transport industry under uncertainty. A multi-company perspective. Issue 5 (3rd April 2020) - Kumar, Aalok; A, Ramesh
Abstract : Purpose: The balancing of sustainability dimensions is the prime agenda of supply chain organisations. The supply chain sustainability greatly influenced by its freight transport activities. Most of the previous work discussed the economic and environmental sustainability of freight transport industry; although the social sustainability (SS) dimension paid less attention to researchers and practitioners of emerging economies. The purpose of this study is to investigate the importance of SS indicators in the freight transport industry. The SS assessment framework is validated with the Indian freight transport industry. Design/methodology/approach: The proposed framework considers four SS dimension and 25 indicators. The SS indicators' importance varies with the individual company's prospect. Therefore the proposed framework is used in multi-company perspective as well as in industry perspective to present more realistic results. The importance weight of SS dimension and indicators are computed with a novel multi-criteria decision-making (MCDM) method, i.e. fuzzy best–worst method (FBWM). Findings: The prioritisation of SS indicators in each company perspective is compared with an industry perspective. The contribution to community health and education program is most valuable indicator followed by the prevention of child and forced labour. The model robustness is tested through sensitivity analysis and reported that less variation in indicators' ranking. Originality/value: To authors best of knowledge, this is the first study to highlight the importance of SS indicators in the freight transport industry. This study contributes to the sustainability assessment literature by providing a nuanced perception of the SS indicators and put forward managerial implications for improving the SS of the freight transport industry. The proposed framework could be treated as a benchmark for other developing nation's freight transport industry.